Answer:
x = 5 or x = 1
Step-by-step explanation:
x² - 6x + 7 = 0
x² - 6x = -7
x² - 6x + 9 = -7 + 9 1/2 of the x term than square it and add it the both sides.
(x - 3)(x - 3) = 2
( x -3)² = 2
= ![\sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
(x - 3) = ± 2
x - 3 = 2 or x - 3 = -2
x = 5 or x = 1
Answer:
its Aor the first option because it has repeated x values making it not a function.
Hi there!
• f(x) = 3x + 1
• g(x) = x² - 6
Then,
According to th' question :-
(f - g)(x) = f(x) - g(x)
= 3x + 1 - (x² - 6)
= 3x + 1 - x² + 6
= -x² + 3x + 7
Hence,
Option 2ⁿᵈ : -x² + 3x + 7 is Correct.
~ Hope it helps!
If 2.5 yields 6 servings then .41666666 cups for 1 serving